How Does It Feel to Be a Pathologist in Turkey? Results of a Survey on Job Satisfaction and Perception of Pathology - Burcin PEHLIVANOGLU; Hur HASSOY; Gulen GUL; Umut AYKUTLU; Basak DOGANAVSARGIL (Türk Patoloji Dergisi, 2021)

(untitled)
Objective: Job satisfaction affects productivity and professional performance in many aspects; however, there is limited data regarding pathologists' job satisfaction. Hence, in this study, we aimed to evaluate surgical pathologists' job satisfaction in Turkey.